Acute flaccid myelitis associated with enterovirus D68 in a non-epidemic setting. (2019) - Hatayama, Kazuki; Goto, Shinichiro; Yashiro, Masato; Mori, Harushi; Fujimoto, Tsuguto; Hanaoka, Nozomu; Tanaka-Taya, Keiko; Zuzan, Tomoka; Inoue, Masaru
Abstract: Acute flaccid myelitis (AFM) is a recently defined clinical disease accompanied by the national outbreak of enterovirus D68 (EV-D68) in the United States during the late summer/fall of 2014; 258 cases of EV-D68 and 59 cases of AFM were reported in Japan during the late summer/fall of 2015. Subsequently, there have been no epidemics of AFM or EV-D68. However, we encountered a patient who had AFM associated with EV-D68 in 2017. This is the first case of AFM caused by EV-D68 after the 2015 epidemic, and the only reported case in 2017. This report indicates that AFM caused by EV-D68 can arise even in non-epidemic situations. If a patient presents with paralysis, AFM caused by EV-D68 should be included in the differential diagnosis, regardless of the absence of an epidemic of EV-D68 infection.